2011
DOI: 10.1128/mcb.01316-10
|View full text |Cite
|
Sign up to set email alerts
|

CCN5, a Novel Transcriptional Repressor of the Transforming Growth Factor β Signaling Pathway

Abstract: CCN5 is a member of the CCN (connective tissue growth factor/cysteine-rich 61/nephroblastoma overexpressed) family and was identified as an estrogen-inducible gene in estrogen receptor-positive cell lines. However, the role of CCN5 in breast carcinogenesis remains unclear. We report here that the CCN5 protein is localized mostly in the cytoplasm and in part in the nucleus of human tumor breast tissue. Using a heterologous transcription assay, we demonstrate that CCN5 can act as a transcriptional repressor pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 54 publications
6
96
1
Order By: Relevance
“…It is reported that CCN3 is present in the nucleus and behaves like a transcription factor therein (Planque et al 2006). Of our interest, CCN5, another CCN family member, actually regulates gene expression in the nucleus (Sabbah et al 2011). Investigation of the mechanism of this CCN3 action is of great scientific interest as well.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that CCN3 is present in the nucleus and behaves like a transcription factor therein (Planque et al 2006). Of our interest, CCN5, another CCN family member, actually regulates gene expression in the nucleus (Sabbah et al 2011). Investigation of the mechanism of this CCN3 action is of great scientific interest as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been discovered to encode a novel secreted adipokine protein that is a negative regulator of preadipocyte commitment (Hammarstedt et al, 2013). It has also been shown to inhibit the pro-fibrotic connective tissue growth factor (Sabbah et al, 2011). Furthermore, WISP2 was recently identified as one of the top candidate secreted proteins in the development of obesity, as determined by fat depot DE between obese and lean humans (Dahlman et al, 2012).…”
Section: Marbling Physiology and Developmentmentioning
confidence: 99%
“…24 WNT1-inducible-signaling pathway protein 2 (WISP-2) (CCN5), a component of the Wnt pathway, mediates growth arrest and blunts TGF-b-induced effects. 25,26 The present study addresses the cellular effects of atorvastatin on hepatic MFB in vitro and in vivo with special emphasis on proliferation, apoptosis and senescence.…”
mentioning
confidence: 99%